Analysis of the Rising Profile of Equitable Interests and their Application to Transfer of Interests in Land under Nigeria Land Law - Afolabi, Solomon O. (NIU Journal of Humanities, 2018)
Equitable interests in property are generally viewed as of lower value, particularly when they are in competition with legal interests. Generally, equitable interests are considered as minor interests, largely unwritten and if written have failed to comply with all the necessary requirements and therefore are vulnerable and may be lost upon sale of the land to a new purchaser. However, the above view of equitable interests has undergone tremendous changes. Given the contributions of equity in validating most transactions which would have been otherwise invalid by strict application of the law, equitable rights have advanced almost to the status of legal rights. This paper discusses the distinction between equitable interests and legal interests in property and analyses the modern enhanced status of equitable interests. This paper also examines the application of the enhanced status of equitable interests to transfer of interests in land in Nigeria. Given the enhanced status of equitable interests in property and its application to property transactions in Nigeria as demonstrated in this paper, it can be asserted that equitable interests in property have transcended the minor interests they were in the traditional view as they have now almost attained the status of legal estates. Thus, the dichotomy between legal interests and equitable interests has lost much significance. The paper therefore recommends that some statutory provisions which exclude equitable interests from the definition of â€œconveyanceâ€ should be amended to include equitable interests as instruments that validly convey interests in land in Nigeria.